Field Trip Integrated Indigenous Knowledge of Betawi Tribe through Video-Making Skills to Improve Species Knowledge - Fajar Adinugraha; Geskia Avikasari Sembiring; Anne Serafin Hutabarat; Wahyu Agustianto (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The objective of this study is to enhance prospective biology teacher students' species knowledge by integrating the field trip method with the indigenous knowledge of the Betawi Tribe, specifically through the skill of making educational videos. The research method employed was a one-group pre-test-post-test design. This study delineates the learning steps, namely stimulation, ethnobiological discussion, exploratory research, video artifact creation, and publication, conducted with active student involvement. The findings revealed that 66.67% of the students demonstrated proficiency in video production. The field trip combined indigenous knowledge with video-making skills, effectively enhancing students' understanding of local plant and animal species commonly used in traditional Betawi cuisine. The improvement in understanding of local plants and animals is evidenced by the increase in post-test scores compared to pre-test scores, showing a gain of 3.67 points or 16.87%. In addition, the Wilcoxon test showed a significant increase in knowledge of species after the learning experience with a Sig. (Asymp. Sig. 2-tailed) of 0.005 < Sig. 0.05. Field trips that integrated the indigenous knowledge of the Betawi Tribe with video-making skills improved students' knowledge of various species. We expect this research to contribute to improving the quality of education by integrating indigenous knowledge with the development of digital skills